Pengaruh Pengawasan dan Pembagian Kerja Terhadap Efktivitas Kerja Karyawan Pada PT. Mujur Timber Kabupaten Tapanuli Tengah - Arlen Simanjuntak (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Supervision and Work Division on Employee Work Effectiveness, both partially and simultaneously, at PT. Mujur Timber, Central Tapanuli Regency. This research employed a quantitative method with descriptive and associative approaches. The sample consisted of 35 employees. Data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination (R²), t-test, and F-test using SPSS version 27. The results indicate that partially, the Supervision variable (X1) has a negative and insignificant effect on Work Effectiveness (Y), with a t-value of -1.368 and a significance value of 0.181 (> 0.05). The Work Division variable (X2) shows a positive but insignificant effect on Work Effectiveness, with a t-value of 1.607 and a significance value of 0.118 (> 0.05). Simultaneously, the F-test results show that the calculated F-value of 1.423 is lower than the F-table value of 3.29, with a significance value of 0.256 (> 0.05), indicating that Supervision and Work Division together do not have a significant effect on Work Effectiveness. The coefficient of determination (R²) of 0.082 demonstrates that the independent variables explain only 8.2% of the variance in Work Effectiveness, while the remaining 91.8% is influenced by other factors not included in this study. Therefore, the hypothesis stating that Supervision and Work Division have a significant effect on Work Effectiveness at PT. Mujur Timber, Central Tapanuli Regency, is not supported.